2008
DOI: 10.1111/j.1461-9563.2007.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Insect‐screened cultivation to reduce the invasion of tomato crops by Bemisia tabaci: modelling the impact on virus disease and vector

Abstract: 1 In two experiments carried out in Guadeloupe, barriers were used to reduce the entry of the virus vector Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) to tomato plots. The barriers erected around the crop were of insect-proof cloth fences (<50 mesh), 1.5 m in height, in the first experiment with a deltamethrintreated, insect-attracting strip facing inwards, and, in the second, with the barrier but no insecticide-treated strip. 2 A mathematical model of epidemic development was fitted to the symptom dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…Contradictory results were obtained on cabbage in Benin since similar nets promoted the development of aphids and the finest mesh size did not improve protection against insect pests (Simon et al 2014). Similarly, modeling approaches used by Holt et al (2008) revealed that nets used on tomato crops without insecticide-treated strips can promote the development of whiteflies.…”
Section: Control Of Insect Pests With Protected Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Contradictory results were obtained on cabbage in Benin since similar nets promoted the development of aphids and the finest mesh size did not improve protection against insect pests (Simon et al 2014). Similarly, modeling approaches used by Holt et al (2008) revealed that nets used on tomato crops without insecticide-treated strips can promote the development of whiteflies.…”
Section: Control Of Insect Pests With Protected Cultivationmentioning
confidence: 99%
“…However, contradictory studies on hot pepper (Capsicum chinense Jacq.) in Uganda (Karungi et al 2013), on cabbage in Benin (Simon et al 2014;Martin et al 2013) and in Kenya (Kiptoo et al 2015), on tomato in Caribbean islands (Holt et al 2008) showed that insect nets provide insufficient protection against insect pests.…”
Section: Control Of Insect Pests With Protected Cultivationmentioning
confidence: 99%
“…Principales plagas y enfermedades que afectan el cultivo en campo. Holt et al (2008), mencionan que la presencia de mosca blanca (Bemisia tabaci) en cantidades y tiempo después del trasplante es directamente proporcional al porcentaje de incidencia de virus en plantas. Se encontró que el 100% de los productores tienen conocimiento de las plagas que afectan el cultivo (Cuadro 3).…”
Section: Resultados Y Discusiónunclassified
“…The use of insect screening to prevent the entry of virus vectors is practiced in plant nurseries and in field cultivation for some horticultural crops. Experiments were designed to reduce the entry of Bemisia tabaci into tomato crops by insect screens, with or without insecticide-treated strips [ 88 ]. A mathematical model was developed using symptom data of tomato yellow leaf curl disease and potato yellow mosaic disease.…”
Section: Epidemiology and Disease Controlmentioning
confidence: 99%